2021
DOI: 10.1021/acs.jafc.1c00643
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial Impact and Distribution of 3-Methyl-2,4-nonanedione in Cognacs and Spirits

Abstract: The aim of this study was to improve our knowledge on the chemical markers of Cognac aromas. We report results concerning the distribution and sensorial impact of 3-methyl-2,4-nonanedione (MND), a well-known compound in aged red wine, reminiscent of anise or "dried fruit", according to its concentration. We assayed first this diketone (solid-phase microextraction (SPME)−gas chromatography (GC)/mass spectrometry (MS), chemical ionization (CI)) in many Cognac samples followed by grappa, brandy, rum, whisky, vodk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…3-Methyl-2,4-nonandione has been reported to be an important compound in aged red wines, reminiscent of anise or "dried fruit" according to its concentration. 26 In this study, 3-methyl-2,4-nonandione was identified for the first time in Baijiu. Notably, it was only detected in J30 Baijiu at levels ranging from 2.21 to 3.31 μg/L and its low aroma threshold (0.17 μg/L in 53% ethanol aqueous solution) makes the extent of its aroma contribution to aged JXX Baijiu significant.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…3-Methyl-2,4-nonandione has been reported to be an important compound in aged red wines, reminiscent of anise or "dried fruit" according to its concentration. 26 In this study, 3-methyl-2,4-nonandione was identified for the first time in Baijiu. Notably, it was only detected in J30 Baijiu at levels ranging from 2.21 to 3.31 μg/L and its low aroma threshold (0.17 μg/L in 53% ethanol aqueous solution) makes the extent of its aroma contribution to aged JXX Baijiu significant.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…3-Methyl-2,4-nonandione has been reported to be an important compound in aged red wines, reminiscent of anise or “dried fruit” according to its concentration . In this study, 3-methyl-2,4-nonandione was identified for the first time in Baijiu.…”
Section: Resultsmentioning
confidence: 91%
“…Their concentrations reach μg/L. This difference in concentration between wines and spirits was already highlighted in the study of another carbonyl compound, 3-methyl-2,4-nonanedione …”
Section: Resultsmentioning
confidence: 94%
“…This difference in concentration between wines and spirits was already highlighted in the study of another carbonyl compound, 3-methyl-2,4-nonanedione. 45 In view of the highly variable concentrations of these two unsaturated aldehydes in wines and spirits, linked to their stability, several hypotheses have been put forward in relation to SO 2 in wines or to environmental conditions (temperature, light, oxygen, metals). Of course, based on our previous investigation on oak wood, 6 these observations raise the question of the contribution of this material to the release of these compounds, i.e., the impact of maturation or aging.…”
Section: Trans-45-epoxy-(e)-2-decenal)mentioning
confidence: 99%
“…Although present in low concentrations in spirits, aldehydes and ketones have a significant olfactory impact because of their low detection thresholds (Ledauphin et al., 2006; Thibaud et al., 2021). 3‐Methyl‐2,4‐nonanedione, whose threshold is only 70 ng/L in 40% (v/v) hydroalcoholic solutions, has been identified as an aroma‐active compound in cognac and other spirits, contributing to the aroma of dried fruits (Thibaud et al., 2021). Acetaldehyde is the primary aldehyde in spirits, providing fruity and cherry aromas at low concentrations and a pungent flavor at high concentrations (Apostolopoulou et al., 2005).…”
Section: Impact Of Traditional Separations On the Aroma Of Fruit Spiritsmentioning
confidence: 99%